EFFECT OF SOME METHODS OF WEED CONTROL ON GROWTH, YIELD AND YIELD COMPONENTS OF TWO CULTIVARS OF BROAD BEAN (VICIA FABA L.) AND ASSOCIATED WEEDS UNDER RAIN FED CONDITION - HASSAN, HADI MURAD; KHETHER, ABBAS ALO (Journal of Duhok University, 2022)
The present study was conducted at Collage of Agricultural Engineering Sciences University of Duhok (Sumel) and Zakho Research Center (Zakho), Kurdistan Region, Iraq, during the growing season 2021-2022 to investigate the effect of different factors includes broad bean cultivars (Aguadulce & Lunga Delle Cascine), herbicide treatments (Control, Basagran 300mL.100L-1, Gallant super 375mL.100L-1, Basagran + Gallant super and Hand weeding) and locations (Sumel and Zakho). The results showed that the Basagran herbicide completely eliminated broad–leaved weeds and Gallant super completely eliminated narrow leaved-weeds. According to study results the best cultivar for Sumel location was Lunga Delle Cascine and Aguadulce for Zakho location. The treatment of Hand weeding in Sumel location and treatment of Gallant super in Zakho location lead to increase all studied parameter